The Use of Total Physical Response Method in Teaching Vocabulary at The Fourth Grade of Al Ma’soem Elementary School - Yanti, Irma; Uyun, Aip Syaepul; Sakina, Rahma (Ma'soem University, 2024)
Total Physical Response (TPR) is one of the methods used in English language teaching. This method was created by James Asher (1964) and is designed to make students more interested and less bored. This study aims to find out whether or not the Total Physical Response method can improve vocabulary acquisition in fourth grade students at Al Ma'soem Elementary School. This study used pre-experiment research. The sample taken was only one class by giving a pre-test and post-test to the experimental group of 25 students. The results of the analysis of the value of t_((0.975)) for a two-sided test on the distribution of students (t) dk = 23 obtained t table = 2.069. From the results of the calculation of t count = 10.360, which is in the H0 rejection area, it is concluded that there is an effect of using the Total Physical Response method in teaching vocabulary to grade IV students.